HR Management Training for Social Organization to Improve Volunteer Effectiveness and Job Satisfcation - Aat Ruchiat Nungraha; Bucky Wibawa Karya Guna; Tri Suparyanto; Dewanto; Tomi Apra santosa; Andri Kurniawan (LPPM Akademi Teknik Adikarya, 2025)
This study aims to analyze the effect of human resource management (HR) training on increasing volunteer effectiveness and job satisfaction in social organizations. Social organizations often face challenges in maximizing volunteer contributions due to a lack of structured management and adequate training. This study uses a quantitative approach with a pretest-posttest experimental design in two groups, namely the experimental group that received training and the control group that did not receive training. The training provided includes time management, communication skills, conflict management, and teamwork development, which is designed to improve the competence of volunteers in supporting organizational goals. The study respondents consisted of 20 volunteers who were active in several social organizations, with data collected through work effectiveness and job satisfaction questionnaires that had been tested for validity and reliability. Data analysis was conducted using independent statistical tests to identify significant differences between the two groups. The results showed that HR management training significantly increased volunteer work effectiveness by 30% and job satisfaction by 22% (p < 0.05). Volunteers who participated in the training reported improved ability to complete tasks, built positive interpersonal relationships, and felt more valued in the organization.